Spectrum imaging and three-dimensional atom probe studies of fine particles in a vanadium micro-alloyed steel - Craven, A; MacKenzie, M; Cerezo, A; Godfrey, T; Clifton, P (2008)
Sub-15 nm vanadium based particles are one of the strengthening mechanisms in vanadium microalloyed high strength low alloy steel. Two analytical methods, spectrum Imaging using electron energy loss spectroscopy (EELS) and three-dimensional atom probe, have been used to characterise such particles in the matrix, confirming the results of an earlier EELS study using extraction replicas where the particles were found to be N rich (V, Cr)(C, N). The present study also showed that the extraction efficiency of particles <4 nm is low. The three-dimensional atom probe showed an 'atmosphere' of segregated atoms around the cores of the particles and this was supported by the EELS results. In addition, it showed that the C concentration in the matrix was close to the equilibrium concentration at 600°C, supporting the explanation that the low C content of the particles was the result of Fe3C formation. Areas where the techniques can be further improved are identified. © 2008 Institute of Materials, Minerals and Mining.